3D Printing for Tissue Engineering. Issue 9 (2nd October 2013) - Richards, Dylan Jack; Tan, Yu; Jia, Jia; Yao, Hai; Mei, Ying
Abstract Tissue engineering aims to fabricate functional tissue for applications in regenerative medicine and drug testing. More recently, 3D printing has shown great promise in tissue fabrication with a structural control from the micro‐ to the macroscale by using a layer‐by‐layer approach. Whether through scaffold‐based or scaffold‐free approaches, the standard for 3D‐printed tissue engineering constructs is to provide a biomimetic structural environment that facilitates tissue formation and promotes host tissue integration (e.g., cellular infiltration, vascularization, and active remodeling). This review will cover several approaches that have advanced the field of 3D printing through novel fabrication methods of tissue engineering constructs. It will also discuss the applications of synthetic and natural materials for 3D printingfacilitated tissue fabrication.